Bandgap Enhancement: Bandgap Control of the Oxygen‐Vacancy‐Induced Two‐Dimensional Electron Gas in SrTiO3 (Adv. Mater. Interfaces 6/2014). Issue 6 (September 2014) - Liu, Z. Q.; Lu, W.; Zeng, S. W.; Deng, J. W.; Huang, Z.; Li, C. J.; Motapothula, M.; Lü, W. M.; Sun, L.; Han, K.; Zhong, J. Q.; Yang, P.; et al.
<x xml:space="preserve">Abstract</x> SrTiO3 to modern oxide electronics is like silicon to the entire semiconductor industry. Z. Q. Liu, Ariando, and co‐workers show in article 1400155 that the bandgap of SrTiO3 can be 20% larger in thin films than in the bulk. Such bandgap enhancement can change several properties. For example, it can vary the electronic and magnetic phases of SrTiO3‐based interface systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>